Permeability: much remains to be done - Weiß, Reinhold [Verfasser] (My University, 2007)
Although some progress has been achieved, a whole series of barriers remain to be overcome in the endeavour for greater permeability. Against this backdrop, the Deputy President and Head of Research at BIBB, Prof. Dr. Reinhold Weiß, points out the different facets of permeability that are relevant for vocational education and training. (BIBB)
Keywords: G 2.5.3 Anschlussfähigkeit von Bildungsgängen; Durchlässigkeit im Bildungssystem; Berufsbildung